Interactions between the mammalian main and accessory olfactory systems - Micheal Baum (Frontiers Research Topics, 2014)
The functional cross-talk and structural interaction between the main and accessory olfactory bulb is a central problem in mammalian sensory neurobiology. The early supposition that volatile substances and pheromones, most of them hydrosoluble molecules, are exclusively sensed and decoded by the main (MOS) and accessory olfactory systems (AOS), respectively, needs to be revised. In fact, a large number of structural and functional evidences accumulated during the last few decades, suggests that rather than separated entities, the MOS and AOS act synergically, bringing about physiological and behavioural responses. The goal of the present Research Topic will be to gather original research studies and revision papers, performed by the most authoritative research groups that have recently contributed to the broad area of sensory neurobiology. Special attention should be given to contributions addressed to the MOB and AOB cross-talk, involving current neuroanatomical techniques.